Application of the weighted histogram method for calculating the thermodynamic parameters of the formation of oligodeoxyribonucleotide duplexes - I. I. Yushin; V. M. Golyshev; D. V. Pyshnyi; A. A. Lomzov (Вавиловский журнал генетики и селекции)
To date, many derivatives and analogs of nucleic acids (NAs) have been developed. Some of them have found uses in scientific research and biomedical applications. Their effective use is based on the data about their properties. Some of the most important physicochemical properties of oligonucleotides are thermodynamic parameters of the formation of their duplexes with DNA and RNA. These parameters can be calculated only for a few NA derivatives: locked NAs, bridged oligonucleotides, and peptide NAs. Existing predictive approaches are based on an analysis of experimental data and the consequent construction of predictive models. The ongoing pilot studies aimed at devising methods for predicting the properties of NAs by computational modeling techniques are based only on knowledge about the structure of oligonucleotides. In this work, we studied the applicability of the weighted histogram analysis method (WHAM) in combination with umbrella sampling to the calculation of thermodynamic parameters of DNA duplex formation (changes in enthalpy ∆H°, entropy ∆S°, and Gibbs free energy          ∆G37° ). A procedure was designed involving WHAM for calculating the hybridization properties of oligodeoxyribonucleotides. Optimal parameters for modeling and calculation of thermodynamic parameters were determined. The feasibility of calculation of ∆H°, ∆S°, and          ∆G37° was demonstrated using a representative sample of 21 oligonucleotides 4–16 nucleotides long with a GC content of 14–100 %. Error of the calculation of the thermodynamic parameters was 11.4, 12.9, and 11.8 % for ∆H°, ∆S°, and          ∆G37° , respectively, and the melting temperature was predicted with an average error of 5.5 °C. Such high accuracy of computations is comparable with the accuracy of the experimental approach and of other methods for calculating the energy of NA duplex formation. In this paper, the use of WHAM for computation of the energy of DNA duplex formation was systematically investigated for the first time. Our results show that a reliable calculation of the hybridization parameters of new NA derivatives is possible, including derivatives not yet synthesized. This work opens up new horizons for a rational design of constructs based on NAs for solving problems in biomedicine and biotechnology.